2010
DOI: 10.1155/2010/103094
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease: Is It a Toxic Syndrome?

Abstract: Parkinson's disease (PD) is one of the neurodegenerative diseases which we can by certainty identify its pathology, however, this confidence disappeares when talking about the cause. A long history of trials, suggestions, and theories tried linking PD to a specific causation. In this paper, a new suggestion is trying to find its way, could it be toxicology? Can we—in the future—look to PD as an occupational disease, in fact, many clues point to the possible toxic responsibility—either total or partial—in causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The process of production of lewy bodies is confirmed by scientists as subordinate to the refractive proteolytic pathway that causes an unusual breakdown or increased production subjected to genetic mutations. It is confirmed that alpha-synuclein modifies dopamine biosynthesis and negatively controls the dopamine transporter system 18,19 . Apart from the mechanisms mentioned above, other various routes are expected to be involved.…”
Section: Pathogenesis Of Pdmentioning
confidence: 88%
See 1 more Smart Citation
“…The process of production of lewy bodies is confirmed by scientists as subordinate to the refractive proteolytic pathway that causes an unusual breakdown or increased production subjected to genetic mutations. It is confirmed that alpha-synuclein modifies dopamine biosynthesis and negatively controls the dopamine transporter system 18,19 . Apart from the mechanisms mentioned above, other various routes are expected to be involved.…”
Section: Pathogenesis Of Pdmentioning
confidence: 88%
“…The complex 1 deficiency understood as the uninterrupted relation between mitochondrial dysfunction and PD in SNPc; this deficiency was also successively observed in skeletal muscles and platelets. DA neurons being more susceptible to oxidative stress resulted in the association of auto-oxidation and DA metabolism, a rise in iron and a fall in total glutathione levels was seen along with mitochondrial complex 1 inhibition that led to surpassing the oxidative capability of DA cells, eventually causing cell death 18 .…”
Section: Pathogenesis Of Pdmentioning
confidence: 99%
“…The misfolded protein behaves like a template inducing conformational change in the wild type proteins causing a cross-reaction and leading to neurodegeneration. Histologically, there is neuronal loss in the substantia nigra pars compacta along with compensatory astrocytic and microglial proliferation and biochemically there is loss of dopaminergic termini in the striatum [21]- [23].…”
Section: Introductionmentioning
confidence: 99%